Stellaluna - Cannon, Janell, 1957- (San Diego : Harcourt Brace Jovanovich, 1993)
After she falls headfirst into a bird's nest, a baby bat is raised like a bird until she is reunited with her mother.
CD: Stellaluna -- Why the bat flies at night -- Hattie, the backstage bat -- Amazing bat facts.
Some copies accompanied by 1 sound disc produced by High Windy Audio, 1996; read by David Holt.
American Booksellers Book of the Year (ABBY) Award, Children's, 1994 http://www.bookweb.org/btw/awards/ABBY.html
Elementary Grade.
Accelerated Reader
Reading Counts!
550
Keywords: Bats -- Juvenile literature; Birds -- Juvenile literature; Bats -- Fiction; Birds -- Fiction